PROMOTING DIGITAL INDUSTRY INVESTMENT AND THAILAND’S ECONOMIC GROWTH - Kasrisom, Arnon (RMUTT Global Business and Economics Review, 2025)
Promoting investment in the digital industry is the foundation for research and development of modern technology and innovation to help stimulate the production process of all manufacturing industries, resulting in continuous and sustainable economic growth and expansion. Analysis of the digital industry's value-added in 2023, the digital industry's value-added reached 2,565,782 million baht, reflecting a growth rate of 14.21%. This represents 14.25% of Thailand's GDP. Compared to 2022, the digital industry's value-added reached 2,326,262 million baht, the digital industry's value-added increased by 239,520 million baht, equivalent to a growth rate of 10.85%. Increased by 3.36% and accounted for 13.29% of GDP, an increase of 0.96%. A total of 132 projects applied for investment promotion in the digital industry, with an investment value of approximately 9.5 billion baht. This represents a decrease from 2022, as that year saw significant investments in digital infrastructure projects. Promote grassroots economy, advocate for changes and amendments to laws, regulations, and rules to support grassroots economy, provide funding for research and development, develop human resources in ICT and digital technology and innovation and promote related industries and provide digital support.